2010
DOI: 10.1002/pdi.1522
|View full text |Cite
|
Sign up to set email alerts
|

The Association of British Clinical Diabetologists (ABCD) nationwide exenatide audit

Abstract: In December 2008, to accelerate understanding of a new agent, the Association of British Clinical Diabetologists (ABCD) launched a nationwide audit on the use of exenatide in clinical practice. A password‐protected online questionnaire for collection of anonymised patient data was established and diabetes specialists in the UK were given persistent encouragement to submit data on their exenatide‐treated patients. Baseline and latest HbA1c, weight, body mass index (BMI), waist circumference, blood pressure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 16 publications
5
51
0
Order By: Relevance
“…14 Patients in the liraglutide audit had mean ± SD BMI of 38.8 kg/m 2 ± 7.2 and HbA1c of 9.39% ± 1.72 and 39.2% of patients were on insulin at liraglutide initiation. We think that the baseline characteristics of patients in the audit were influenced by NICE guidelines (recommending selection of patients with higher BMI) as well as the predominant participation and use of GLP-1ra therapies in specialist practice dealing with patients with more advanced diabetes.…”
Section: The Abcd Nationwide Glp-1ra Auditsmentioning
confidence: 99%
“…14 Patients in the liraglutide audit had mean ± SD BMI of 38.8 kg/m 2 ± 7.2 and HbA1c of 9.39% ± 1.72 and 39.2% of patients were on insulin at liraglutide initiation. We think that the baseline characteristics of patients in the audit were influenced by NICE guidelines (recommending selection of patients with higher BMI) as well as the predominant participation and use of GLP-1ra therapies in specialist practice dealing with patients with more advanced diabetes.…”
Section: The Abcd Nationwide Glp-1ra Auditsmentioning
confidence: 99%
“…27 It is clear that clinicians in the UK who are treating patients with exenatide and liraglutide, see considerable benefits in terms of reductions in weight and Hba1c; and reduction in other therapies, including insulin. 23,33,34 This audit is in keeping with the everyday experience of clinicians who treat 'real-world' Type 2 diabetes patients on a daily basis and who see benefits with these agents. Those same clinicians hardly ever find their exenatide and liraglutide-treated patients experiencing acute pancreatitis, and when they do, Comparison between the reported rates of acute pancreatitis (cases/100 patient-years of exposure) in the ABCD Nationwide Liraglutide Audit and those in the combined clinical trials of liraglutide, 30 including the rates of those on active comparators in those trials.…”
Section: Discussionmentioning
confidence: 88%
“…Although exenatide was less effective in lowering HbA 1c among insulin-treated patients, a significant number of these insulin-treated patients still achieved significant reductions in HbA 1c , weight and insulin doses. 21,22 There is extremely limited evidence for the use of GLP-1 agonists along with insulin in long-standing type 1 diabetes and this is currently not licensed. One small trial of 11 patients on CSII treatment showed a weight loss of 4.2 per cent and a reduction in insulin requirement of 19.2 per cent when liraglutide was added.…”
Section: Combination Of Insulin and Glp-1 Agonistsmentioning
confidence: 99%